KEJADIAN STUNTING PADA BALITA USIA 3-5 TAHUN DI DESA SIDOREJO JETIS MOJOKERTO - Saudah, Noer; Dewi, Ariu (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Stunting or short stature was a chronic malnutrition condition which occurs linear growth disorder in children. Short children was related with motor development and poor mental, cognitive achievement and poor school performance and has a behavioral problem. Incidence of stunting often enough, but very little data about epidemiology of stunting. The aim of the study was knowed the incidence of stunting in children aged 3-5 years in the Sidorejo village Jetis Mojokerto. Design of this research is descriptive research design. The sampling method used simple random sampling (Probability Sampling). Sample taken as many as 90 respondent aged 3-5 years in the Sidorejo village Jetis Mojokerto on April 2015. The research data was taken with the height measurement. After tabulated, data is analyzed by a frequency distribution table with SPSS to find a mode of research. The results showed 16 children (17.78%) had short stature (stunting), 73 children (81,11%) had normal height and thin children is 1 respondent (1,11%). Although not show a high incidence but need to get the attention of local society to prevent and finished incidence of stunting (short stature). So to reduce the incidence of stunting the most important opportunities to improve child nutrition.Keywords: Child, stunting, height